2013
DOI: 10.1002/j.1532-2149.2013.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Fear‐learning deficits in subjects with fibromyalgia syndrome?

Abstract: Background Fibromyalgia syndrome (FMS) is frequently associated with psychiatric conditions, particularly anxiety. Deficits in contingency learning during fear conditioning have been hypothesized to increase anxiety and, consequently, pain sensation in susceptible individuals. The goal of this study was to examine the relationship between contingency learning and pain experience in subjects with FMS and rheumatoid arthritis (RA). Methods Fourteen female FMS subjects, 14 age-matched female RA subjects and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 48 publications
(57 reference statements)
1
41
2
Order By: Relevance
“…This corroborates earlier findings by Meulders et al [24; 25] demonstrating in a voluntary joystick movement paradigm, in which one movement (CS+) was consistently followed by a noxious electrocutaneous stimulus and another movement (CS-) was not, that FM patients acquired differential fear of movement-related pain to the same extent as the HC group, albeit slower. These findings however contradict those of Jenewein et al [15] showing learning deficits in FM patients compared to patients with osteoarthritis and HC in a differential fear conditioning paradigm using geometrical figures as CSs and a painful heat stimulus as US.…”
Section: Discussioncontrasting
confidence: 99%
“…This corroborates earlier findings by Meulders et al [24; 25] demonstrating in a voluntary joystick movement paradigm, in which one movement (CS+) was consistently followed by a noxious electrocutaneous stimulus and another movement (CS-) was not, that FM patients acquired differential fear of movement-related pain to the same extent as the HC group, albeit slower. These findings however contradict those of Jenewein et al [15] showing learning deficits in FM patients compared to patients with osteoarthritis and HC in a differential fear conditioning paradigm using geometrical figures as CSs and a painful heat stimulus as US.…”
Section: Discussioncontrasting
confidence: 99%
“…These results contradict the findings of Jenewein et al, 32 demonstrating that only 50% of the patients with FM were contingency aware as compared with 100% and 86% of the HC and the osteoarthritis group, respectively. This finding might be associated with the less clear-cut contingencies in their study.…”
Section: Discussioncontrasting
confidence: 97%
“…Using the same experiment in our own previous study, we showed potentially pathogenic associations between fear and pain in individuals with fibromyalgia. 13 Because of the strong association between PTSD and pain, this experiment, which used a painful US that allowed us to assess pain perception, seemed to qualify for the investigation of the pathophysiology of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…13 Before the experiment, study participants were instructed that they would see shapes on a screen in front of them and feel heat bursts on their hand, but we did not provide any information about the relationship between these 2 stimuli. Thermal stimulation and the recording of physiological activity (skin conductance) were controlled using a BIOPAC MP150 System (Biopac Systems, Inc, Goleta, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation